Solution of nonlinear Volterra integro-differential equations of the second kind using Accelerated Adomian Polynomials - Ahmed Y. Sayed; Emad A. Sayed; Rashwan, Mahmoud H.; I. L. El-Kalla (International Journal of Psychosocial Rehabilitation, 2020)
In this paper, an accelerated Adomian polynomials deduced by EL-Kalla (2005, 2007) are used to solve a class of nonlinear integro-differential equations. Some examples investigated and it has found that EL-Kalla formula converges rapidly than the traditional formula of Adomian and the Laplace-Adomian modification, moreover it is programmable, and it saves time to get the approximate solutions with the same version of Matlab. Also, error analysis is established for every example.